Temporal variability in the importance of hydrologic, biotic, and climatic descriptors of dissolved oxygen dynamics in a shallow tidal‐marsh creek. Issue 8 (18th August 2017) - Nelson, Natalie G.; Muñoz‐Carpena, Rafael; Neale, Patrick J.; Tzortziou, Maria; Megonigal, J. Patrick
Abstract: Due to strong abiotic forcing, dissolved oxygen (DO) in shallow tidal creeks often disobeys the conventional explanation of general aquatic DO cycling as biologically regulated. In the present work, we seek to quantify the relative importance of abiotic (hydrologic and climatic), and biotic (primary productivity as represented by chlorophyll‐ a ) descriptors of tidal creek DO. By fitting multiple linear regression models of DO to hourly chlorophyll‐ a, water quality, hydrology, and weather data collected in a tidal creek of a Chesapeake Bay marsh (Maryland, USA), temporal shifts (summer‐early winter) in the relative importance of tidal creek DO descriptors were uncovered. Moreover, this analysis identified an alternative approach to evaluating tidal stage as a driver of DO by dividing stage into two DO‐relevant variables: stage above and below bankfull depth. Within the hydrologic variable class, stage below bankfull depth dominated as an important descriptor, thus highlighting the role of pore water drainage and mixing as influential processes forcing tidal creek DO. Study findings suggest that tidal creek DO dynamics are explained by a balance of hydrologic, climatic, and biotic descriptors during warmer seasons due to many of these variables (i.e., chlorophyll‐ a, water temperature) acting as tracers of estuarine‐marsh water mixing; conversely, in early winter months when estuarine and marsh waters differ less distinctly, hydrologic variables increase in relative importance as descriptors of tidal creek DO. These findings underline important distinctions in the underlying mechanisms dictating DO variability in shallow tidal marsh‐creek environments relative to open water estuarine systems. Key Points: Hydrologic variables increased in relative importance as descriptors of tidal creek DO when transitioning from summer to early winter Bankfull depth was estimated from hydrologic monitoring data and used to divide stage into variables that were relevant to DO dynamics Tidal cycle scale variability and pore water drainage explained much of the temporal variability in DO descriptor importance